Spatial and Physical Transformation Based on Habraken’s Variables in Jatiluwih, Bali - Ni Made Diah Ayu Kendran (Jurnal Arsitektur, 2026)
Jatiluwih Traditional Village is a tourist village in Penebel District, Tabanan Regency, Bali, renowned for its beautiful rice fields. After UNESCO designated its subak system as part of the world cultural heritage in 2012, the village has continued to experience significant tourism development. The entry of a new economic-tourism system indirectly caused changes in the village's spatial pattern, which previously relied solely on the agricultural sector. Change as a form of development effort is indeed inevitable, however, changes that occur quickly and poorly planned can backfire on the village's development. Therefore, this study aims to determine the level of environmental transformation that occurred in Jatiluwih Village as a result of the influx of economic-tourism influences. This study used direct observation methods in several residents' homes and indirect mapping observations via Google Earth. Data analysis was carried out by adopting the transformation variables proposed by N.J. Habraken. Based on these observations, it was found that several residential buildings and agricultural land areas experienced a shift in function due to the growing tourism activity. This research is intended to anticipate spontaneous changes in village spatial planning due to uncontrolled building growth and tourism activities.